Hormone rhythms of the endocrine pancreas: from the chronobiological fundamentals to the clinical implications - Delattre, Edson (Medicina (Ribeirao Preto), 2004)
Initially the theoretical basis for the knowledge of the endocrine rhythms are presented, by taking into consideration that all hormonal secretions display stressed oscillations that denotes a high degree of temporal organization in the endocrine system. Next, the work reviews the rhythm of the endocrine pancreas, by pointing out the circadian and ultradian rhythms of insulin, due to its importance for the physiology and physiopathology of that organ. Both the results secured in vitro and those noticed clinically are presented. The biological reasons for the pulsatile hormones secretion in general are discussed as well as changes of that rhythm, in endocrine pancreas pathologies.